Outcomes for the first wave of hospitalised patients with COVID‐19 in the South Australian context: a retrospective audit. Issue 2 (25th February 2021) - Toh, Dylan J.‐W.; Rowe, Emily; Nelson, Renjy; O'Connell, Alice; Lim, Ken; Fielke, Lauren; He, Jiacheng; Faunt, Jeffrey
Abstract: Background: The first case of corona virus disease (COVID‐19) was detected in South Australia on 1 February 2020. The Royal Adelaide Hospital (RAH) is the state's designated quarantine hospital. Aim: To determine the characteristics, outcomes and predictors of outcomes for hospitalised patients with coronavirus disease (COVID‐19) within the RAH. Methods: We performed a retrospective audit of 103 patients diagnosed with COVID‐19 who were discharged from the RAH between 14 February and 21 May 2020. We collected demographic, clinical and laboratory data through an audit of electronic medical records. The main outcome measures were: (i) the need for oxygen supplementation; (ii) need for intensive care unit (ICU) care; and (iii) death in hospital. Results: The median age of patients was 60 years (range 19–85). A total of 55 (53%) patients was male. All patients were independent at baseline; 37 (36%) patients suffered from hypertension. Cardiovascular disease, respiratory disease and diabetes were present in fewer than 19 (18%) patients. Obesity was present in 24 (23%) patients; 39 (38%) patients required supplemental oxygen, 18 (17%) required ICU care and 4 (4%) patients died. Older patients were significantly more at risk of oxygen requirement (median 68 vs 57.5 years, P < 0.01), ICU admission (median 66.5 vs 60 years, P = 0.04) and death (median 74.5 vs 60 years, P = 0.02). We did not find a statistically significant association between gender, body mass index and poor outcomes. Lactate dehydrogenase (LDH) was the only parameter at admission associated with oxygen requirement, ICU care and death. Peak LDH, aspartate aminotransferase, alanine aminotransferase, C‐reactive protein and neutrophil lymphocyte ratio were significantly associated with oxygen requirement, ICU admission and death ( P < 0.05 for all of the above laboratory markers). Conclusions: Although our sample size was small, we found that certain comorbidities and laboratory values were associated with poor outcomes. This occurred in a setting where care was not influenced by limited hospital and intensive care beds.